Chapter Il diritto del lavoro tra libertà, riconoscimento e non-dominio - perulli, adalberto (Studi e saggi, 2022)
The essay deals with the issue of freedom in labor law through dialogue with two currents of philosophical-political thought: neo-republicanism and the neo-Hegelian theory of social freedom. After the critique of neoliberal economic thought, labor law can draw on these two currents of political philosophy to consolidate, from an evolutionary point of view, its own value paradigm and to identify a new regulatory project that lives up to the challenge of neo-modernity. The ideas of freedom as non-domination and as social freedom, unlike the classical liberal concept of negative freedom, converge in the construction of social rights, such as codetermination, around which to found a new course of labor law.